ARARAS-CANINDÉ (ARA ARARAUNA) EM ÁREA URBANA COMO BIOINDICADORAS DE QUALIDADE AMBIENTAL - MARIA EDUARDA MONTEIRO NASCIMENTO (2024)
The fragmentation and urbanization of habitats impact the lives of animals, as they end up being exposed to non-natural stressors, such as intense air pollution. This contamination releases compounds with mutagenic properties, which can affect biodiversity as a whole. Understanding the interactions between organisms and the environment is of utmost importance. Biomarkers have been used as they allow the observation of early biological effects related to genotoxic agents present in the environment. Birds are considered excellent indicators of environmental quality, as they are sensitive to variations in environmental conditions and respond quickly to changes, especially birds living in urban environments, where they are more exposed to pollution. Thus, the objective of this study was to evaluate the bioindicator potential of blue-and-yellow macaw (Ara ararauna) chicks in an urban ecosystem through genotoxicity tests and environmental factors. A total of 45 samples were collected. The presence/absence and quantity of micronuclei and other nuclear abnormalities were analyzed on slides stained with the May-Grunwald Giemsa technique, observing 5,000 erythrocytes per individual (2.500 cells on each slide). We observed 37 micronuclei and 1047 other nuclear abnormalities, the most common being cells with notched nuclei (44.6%) and the least frequent being anucleated cells (2.8%). Principal component analysis (PCA) was performed to assess the existence of environmental similarities between the nests, as well as broken-stick analysis. From the selection of important variables in this segregation, the data were analyzed in generalized linear models (GLMs). The proportion of nuclear abnormalities was higher in chicks from nests located in areas with higher vehicle traffic and absence or greater distance from green areas. These findings may contribute to future studies on the impacts of urbanization on the genetic health of this species and to a more comprehensive understanding of the effects of human activities on the environment and wildlife.